Pengaruh Simulasi First Aid Kegawatdaruratan Kecelakaan terhadap Pengetahuan Penanganan Fraktur di SMA N 1 Lhokseumawe - Ramadhina Ramadhina; Adi Rizka; Iskandar Albin (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Fractures are conditions where there is a separation or rupture in the continuity of the bone structure, caused by excessive pressure that the bone cannot withstand. According to the World Health Organization (WHO), the incidence of fractures is expected to increase with the growing number of vehicles. The productive age group is particularly vulnerable to injury due to accidents. A lack of knowledge about fractures and First Aid methods can exacerbate the situation. This study aims to determine the impact of fracture education and First Aid simulation methods on the knowledge of students at SMA N 1 Lhokseumawe. The research used a quantitative quasi-experimental design with a one-group pretest-posttest design, involving 91 students. The instrument used was a knowledge questionnaire. The results showed that before the education and simulation, 44 respondents (48.4%) had a poor knowledge category, while after the education and simulation, 84 respondents (93.4%) were in the good category. The Wilcoxon test resulted in a P-value of 0.000, indicating a significant impact. The conclusion of this study is that fracture education and First Aid simulation methods are effective in improving students' knowledge about fractures and First Aid.